2003
DOI: 10.1016/s0095-0696(02)00041-4
|View full text |Cite
|
Sign up to set email alerts
|

Further tests of entreaties to avoid hypothetical bias in referendum contingent valuation

Abstract: Over-estimation of willingness to pay in contingent markets has been attributed largely to hypothetical bias. One promising approach for avoiding hypothetical bias is to tell respondents enough about such bias that they self-correct for it. A script designed for this purpose by Cummings and Taylor was used in hypothetical referenda that differed in payment amount. In comparisons with behavior observed in otherwise identical real payment referenda, the script worked remarkably well at higher payment levels (dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(66 citation statements)
references
References 15 publications
(27 reference statements)
3
59
0
3
Order By: Relevance
“…The effect of cheap talk is, however, ambiguous in the literature. While some studies find that hypothetical bias is reduced (Aadland and Caplan 2003, Brown et al 2003, Champ at al. 2009, Moser et al 2014 other studies find no effect of cheap talk (Blumenschein et al 2008) or that it even exacerbates hypothetical bias Brown 2009, Aadland andCaplan 2006).…”
Section: Related Literaturementioning
confidence: 96%
“…The effect of cheap talk is, however, ambiguous in the literature. While some studies find that hypothetical bias is reduced (Aadland and Caplan 2003, Brown et al 2003, Champ at al. 2009, Moser et al 2014 other studies find no effect of cheap talk (Blumenschein et al 2008) or that it even exacerbates hypothetical bias Brown 2009, Aadland andCaplan 2006).…”
Section: Related Literaturementioning
confidence: 96%
“…Cummings and Taylor's (1999) paper stimulated several other tests of cheap talk scripts. Brown et al (2003), in another public good referendum study with student subjects, tested the Cummings and Taylor (1999) cheap talk script at several bid levels. They found that the script was effective at an $8 bid level, but was less effective or ineffective at lower bid levels.…”
mentioning
confidence: 99%
“…The cheap talk approach (Cummings and Taylor 1999), for example, is a popular calibration technique in which the hypothetical bias problem is described to subjects. Yet, the effectiveness of this approach may be sensitive to key variables such as script length (Poe et al 2002;Aadland and Caplan 2003), subject experience (List 2001;Lusk 2003;Aadland and Caplan 2003) and payment amounts (Brown et al 2003;Murphy et al 2005b). In fact, Aadland and Caplan (2006) find that a neutral cheap talk script can actually exacerbate hypothetical bias.…”
mentioning
confidence: 99%